Avaliação em queijos Minas frescal provenientes do Sudoeste de Minas Gerais da presença de fatores de virulência e resistência antimicrobiana em isolados de Escherichia coli - Okura, Mõnica Hitomi [UNESP]; Marin, José Moacir (My University, 2014)
The soft cheese Minas frescal is one of the most popular cheese in Brazil, which is typically manufactured in small dairy farms under unsatisfactory hygiene conditions. To assess the risk involved in consumption of this cheese, virulence markers were investigated in 330 Escherichia coli strains isolated from 30 Minas frescal cheeses inspected by official government agency (SIF - serviço de inspeção federal), from 50 cheeses not inspected by SIF and 31 cheeses not inspected by SIF with spice added, all of them collected in the southwest of Minas Gerais State. The E. coli isolates were screened for the presence of Shiga toxin-encoding (stx 1 and stx 2), intimin (eae) genes and for the presence of (pap, sfa, afa) genes related to adhesion in epithelial cells. The only gene detected by PCR was the sfa gene at one isolate. The strains were also screened for resistance to 9 antimicrobial drugs. Predominant resistance was to cephalothin, tetracycline and streptomycin. Multidrug resistance was found among isolates from cheese with SIF (16.6%), cheese without SIF (8.0%) and cheese without SIF with spice added (30.0%) what is a reason for concern due to the high consumption of raw milk cheese by the Brazilian population.
Survey of Minas frescal cheese from Southwest Minas Gerais for virulence factors and antimicrobial resistance in Escherichia coli isolates
Keywords: Antimicrobial resistance; Cheese; Escherichia coli; ExPEC; Minas frescal; STEC